Kajian Ekonomi Rencana PLTMH di Desa Panji - Suatan, Richard Antony; Giriantari, Ida Ayu Dwi; Sukerayasa, I Wayan (Majalah Ilmiah Teknologi Elektro; Vol 19 No 2 (2020): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2020.v19i02.P20, 2020)
The micro hydro power plant (PLTMH) in Banjar Dinas Mekar Sari, was built independently by community groups in 1980. With the use of traditional technology, the efficiency of PLTMH is low, so it is necessary to re-plan for PLTMH Banjar Dinas Mekar Sari to operate more optimally.. One of the most important factors in planning is financial / economic factors. This factor will be used to assess a plan whether it is feasible to build or not. The parameters used in determining economic factors are Net Present Value (NPV, Internal Rate of Return (IRR), Benefit to Cost Ratio (BCR), Life Cycle Cost (LCC), and Break Even Point (BEP). Economic feasibility analysis has been carried out. for planning PLTMH Banjar Dinas Mekar Sari obtained, BCR of 0.23 and -0.08 and NPV value of Rp.476,747,506 and -Rp.161,451,546 are positive when the discount rate is 10% and negative when the discount value is 12%, and the amount of the IRR value 1% and 0% do not exceed Indonesia's Expected Annual Rate of Return, which is 14.6%, and the amount of BEP units that must be sold to reach a cash flow point is Rp. 0 of 2,294,914.96 kWh, and the amount of payback period at This project is 2 years 2 months. So seen from the existing economic parameters, the design of PLTMH in Banjar Dinas Mekar Sari is not feasible from an economic point of view because the large profits obtained from the design of PLTMH Banjar Dinas Bembang Sari do not exceed the initial start. al cost (investment cost).